2016
DOI: 10.1093/imrn/rnv376
|View full text |Cite
|
Sign up to set email alerts
|

There Are Infinitely Many Rational Diophantine Sextuples

Abstract: A rational Diophantine m-tuple is a set of m nonzero rationals such that the product of any two of them increased by 1 is a perfect square. The first rational Diophantine quadruple was found by Diophantus, while Euler proved that there are infinitely many rational Diophantine quintuples. In 1999, Gibbs found the first example of a rational Diophantine sextuple. In this paper, we prove that there exist infinitely many rational Diophantine sextuples. set 1 16 , 33 16 , 17 4 , 105 16 found by Diophantus (see [4])… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 23 publications
0
56
0
Order By: Relevance
“…A long-standing conjecture, motivated by work of Baker and Davenport [1], that there is no Diophantine quintuple, was recently proven [7]. At a similar time, in [4], it was found that there are infinitely many Diophantine sextuples in rational numbers. Generalizing results from integers to rationals can be very hard.…”
Section: Introductionmentioning
confidence: 99%
“…A long-standing conjecture, motivated by work of Baker and Davenport [1], that there is no Diophantine quintuple, was recently proven [7]. At a similar time, in [4], it was found that there are infinitely many Diophantine sextuples in rational numbers. Generalizing results from integers to rationals can be very hard.…”
Section: Introductionmentioning
confidence: 99%
“…Let us mention that there exist a polynomial D(n)-sextuple in Z[X], where n is not a constant polynomial (see [19,20]). Moreover, in all those examples n is a square in Z[X], while for n ∈ Z[X] non-square, there exist examples of D(n)quintuples in Z[X] (see [14]).…”
Section: Diophantus Of Alexandriamentioning
confidence: 99%
“…Third curve. In a recent paper [9] it is shown the existence of infinitely many rational Diophantine sextuples. In the proof elliptic curves are used in order to extend a family of rational Diophantine triples to a family of sextuples.…”
Section: 2mentioning
confidence: 99%